Significance of elastic deformation on radiative flow of tangent hyperbolic hybrid nanofluid with application of Cattaneo-Christov model - Abbas, Munawar; Khan, Nargis; Mohammad, Alsharef; Hashmi, M. S.; İnç, Mustafa (Wiley-V C H Verlag Gmbh, 2025)
This study investigates the chemical reactive flow of MHD is impacted by a non-uniform heat source. A tangent hyperbolic hybrid nanofluid across a plate in a permeable media with heat radiation is examined in relation to elastic deformation. Additionally, it investigates the effect of activation energy. The radiative flow of tangent hyperbolic hybrid nanofluid with elastic deformation is a significant application of the Cattaneo-Christov model in advanced thermal management systems. It is essential for applications requiring precise control of heat and mass transfer, such as biomedical engineering, wastewater treatment, and nano-microfluidic devices. The performance of cooling and heating processes based on nanofluids in nuclear reactors, energy storage, and electronic cooling systems is improved by the use of elastic deformation effects. Additionally, this model improves the accuracy of thermal predictions by shedding light on non-Newtonian hybrid nanofluids in biological systems where heat conduction follows a non-Fourier mechanism, such as tissue engineering. The fundamental governing PDEs are converted to ODEs by adopting similarity variables. Bvp4c method is used to solve nonlinear ODEs. The concentration and temperature distributions reduce as the elastic deformation parameter increases.
Keywords: Mass-Transfer; Mhd Flow